IMPLEMENTATION OF THE GOOGLE FORM APPLICATION TO ADMINISTRATOR LEADERSHIP TRAINING ACTIVITIES AT THE HUMAN RESOURCES DEVELOPMENT AGENCY IN BENGKULU PROVINCE - Muhammad Rivandy Setiawan; A. Ramadanni (Post Graduate School of Government Science, 2022)
Technological developments in terms of attendance allow event organizers or agencies to record attendance more easily. Before there was digital attendance filling, all were filled manually with paper and signatures. As a result, it is often difficult to record attendance and it takes a long time to record attendance. Currently, an example of technology that is present to overcome problems in attendance is the use of Google Forms. Google Forms is an application from Google that is general in nature and can be accessed at no cost or free. Google Forms can be used across a variety of devices. This study aims to determine the effectiveness of using Google Forms in filling attendance at the HRD Agency OF Bengkulu Province. The research method used is a qualitative research method with a descriptive approach. Collecting data by means of observation, interviews, documentation, and focus group discussions. As a result, participants and organizers found it helpful to use Google Forms for attendance, plus the signature of each participant when filling out attendance. The use of Google Forms in organizing apparatus leadership training activities at the HRD Agency of Bengkulu Province can be available for free, easy to operate, and can be accessed anywhere and anytime. The problems faced are sometimes unstable networks, PICs who still don't have a Google account, and some participants who still don't understand how to fill out Google Forms. Efforts made by HRD Agency of Bengkulu Province were to replace the wifi network with a personal data network, conduct a brief socialization of the creation of a Google account as well as the creation of a Google Form, and socialize to participants about filling out Google Forms to completion.